(untitled) (Asian Journal of Ethnobiology, 2021)
Abstract. Enebeli-ekwutoziam KC, Aruah CB, Ogbonna BO, Eze UJ, Egedeye-fubura FS, Nwankwo CF, Oliseyenum IN, Udoha NW, Afuye TN, Asogwa GN, Chinweokwu KA, Anenih FO, Iyamu JE, Oboti ID, Nwaizu N, Ajabor JI, Ozadibe OY, Otunla RA, Francis OB, Orji CM. 2021. Ethnomedicinal survey of plants used in the treatment of skin-related ailments in the Northern Delta State of Nigeria. Asian J Ethnobiol 4: 76-85. An ethnomedicinal survey of plants used to treat skin-related ailments was conducted to document information on the common plant resources employed in the ethnomedicinal practices of the indigenous people of the Northern Delta State of Nigeria. A total number of 100 respondents were selected from the Northern Delta State of Nigeria. The herbalists were mostly males (61%). The respondents comprised two age groups, i.e. <40 (30%), and >40 (70%). The respondents were 30 herbal drug dealers, 46 herbalists, and 24 community elders. Semi-structured questionnaires were used to obtain data through personal interviews with the respondents. 51 plant species belonging to 29 families of flowering plants were revealed as useful in the treatment and management of Skin diseases/parasites, boils, wounds, cuts, sores, pimples, inflammation, aftershave bumps, abscess, and bleeding. Asteraceae (8.75) and Fabaceae (8.2) showed the best consensus among respondents on reported species and families. The highest values of relative citation frequencies were reported for Citrus limon and Ricinus communis with 0.24 each. On the other hand, the highest value of fidelity level was reported for Elaeis guineensis (99). Herbs were the most dominant life form found in the study (45%). Females (52%) have higher knowledge of medicinal plants and their application than males (48%). Leaf was the most commonly used plant part (44%) in preparing herbal remedies. A decoction was the most common method of herbal drug preparation (33.96%). Herbal recipes used by the locals to treat skin-related ailments contain some active ingredients, some of which have been scientifically proven and others still undergoing clinical validation. This justifies their ethnomedicinal uses as a remedy for skin ailments. High levels of medicinal plant diversity and ethnomedicinal knowledge exist in the area. Therefore conservation studies should be carried out on the plants reported in this survey for sustainability.